Sustainable Legal Framework for Transboundary Movement of Electronic Waste - Christian, Gideon (Université d'Ottawa / University of Ottawa, 2014)
The quest for sustainable development has always involved the complex task of reconciling the need for socio-economic development with public health and environmental protection. This challenge has often emerged in the trade and environment debate but has most recently been evident in international trade in used electrical and electronic equipment (UEEE). While international trade in UEEE provides means for socio-economic development in the developing world, it also serves as a conduit for transboundary dumping of e-waste in the developing world giving rise to serious health and environmental concerns. This research investigates the socio-economic as well as health and environmental impacts of international trade in UEEE in two developing countries – Nigeria and Ghana. The research identifies a major loophole in the existing international legal framework as the primary factor responsible for e-waste dumping in the developing world. This loophole relates to the absence of a legal framework for differentiating between functional UEEE and junk e-waste. This has resulted in both functional UEEE and junk e-waste being concurrently shipped to the developing world as “used electrical and electronic equipment”. The research proposes two policy frameworks for addressing this problem. On the part of developing countries, the research proposes a trade policy framework crafted in line with WTO rules. This framework will entail the development of an international certification system which will serve to differentiate functional used electronics from junk e-waste. While the former may be eligible for import, the research proposes an import ban on the latter. On the part of developed countries, the research proposes the development of a policy framework which regulates the toxic and hazardous substances that go into the production of electrical and electronic equipment as well as enhance their reusability and recyclability at end-of-life. The framework should take into consideration the entire life cycle of the products from the design stage to end-of-life. The research argues that the implementation of this design framework will go a long way in reducing the health and environmental impacts of such equipment when subsequently shipped to the developing world at end-of-life.
Keywords: Basel convention; e-waste; environmental justice; EPR; hazardous waste; international trade; recycling; sustainable development; trade restriction